2019
DOI: 10.1021/acscatal.9b03894
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Dehydrative Peptide Synthesis with gem-Diboronic Acids

Abstract: Alkane-gem-diboronic acids have emerged as versatile organoboron catalysts for dehydrative amidation of α-amino acids. A phenol-substituted multiboron catalyst with a B–C–B structure outperformed simple arylboronic acids in the condensation of α-amino acids with suppressed epimerization of electrophiles. gem-diboronic acid catalysis were compatible with various O, N, and S-functionalized α-amino acids bearing N-protecting groups including common carbamates used in peptide synthesis (Boc, Cbz, Fmoc). N-trifluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Taking a step forward, a 2-chloro-substituted biaryl boronic acid 25 was observed efficiently catalyzing the peptide bond condensations, giving fourteen desired dipeptides in good yields with little to no racemization ( Figure 12 C) [ 73 ]. Takemoto’s group devised an ortho-hydroxyphenyl-substituted gem-diboronic acid 26 capable of catalyzing peptide condensations ( Figure 12 C) [ 74 ]. It was found that the gem-diboronic acid catalyst could efficiently activate the carboxy group of α-amino acids by forming bidentate intermediates, which then led to amidation by nucleophilic amino acids to afford the corresponding dipeptides.…”
Section: Boronic Acid-mediated Peptide Synthesis and Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking a step forward, a 2-chloro-substituted biaryl boronic acid 25 was observed efficiently catalyzing the peptide bond condensations, giving fourteen desired dipeptides in good yields with little to no racemization ( Figure 12 C) [ 73 ]. Takemoto’s group devised an ortho-hydroxyphenyl-substituted gem-diboronic acid 26 capable of catalyzing peptide condensations ( Figure 12 C) [ 74 ]. It was found that the gem-diboronic acid catalyst could efficiently activate the carboxy group of α-amino acids by forming bidentate intermediates, which then led to amidation by nucleophilic amino acids to afford the corresponding dipeptides.…”
Section: Boronic Acid-mediated Peptide Synthesis and Modificationsmentioning
confidence: 99%
“…It was found that the gem-diboronic acid catalyst could efficiently activate the carboxy group of α-amino acids by forming bidentate intermediates, which then led to amidation by nucleophilic amino acids to afford the corresponding dipeptides. Interestingly, the catalyst was compatible with α-amino acids bearing several different N-protecting groups, such as Boc, Cbz, Fmoc, and N-trifluoroacetyl, and activated their carboxy groups to furnish the desirable dipeptides in good yields with low epimerization [ 74 ]. Moreover, nucleophilic amino acids endowed with a variety of functionalized side chains including phenyl, alkyne, sulfide, ester, amide, and imidazole were also tolerated, which implies the versatility of this strategy.…”
Section: Boronic Acid-mediated Peptide Synthesis and Modificationsmentioning
confidence: 99%
“…Therefore, the development of an environmentally benign catalytic version of the dehydrative amide condensation reaction is highly demanded (Scheme 1a). Starting with Yamamoto's pioneering report on the catalytic dehydrative amide condensation of carboxylic acids with amines using electron-deficient aromatic boronic acids, 14 a variety of amidations and peptide synthesis utilizing organoboron catalysts, such as modified aromatic boronic acids, [15][16][17][18] diboron, 19 borate esters, 20 DATB, 21 and gem-diboronic acid, 22 have been developed. In this context, we disclosed that a diboronic acid anhydride possessing the B-O-B motif 23 is a highly efficient catalyst for the dehydrative amidation of or -hydroxycarboxylic acids 24a or -hydroxy--amino acids.…”
Section: Catalytic Synthesis Of Serine-and Threonine-derived Weinreb Amidesmentioning
confidence: 99%
“…Acidity has a def ining role in numerous chemical and biological processes [1] , for example, the activity of enzymes [2] , the assembly of DNA [3] and the solid phase synthesis of biopolymers using acid or basic labile protecting groups [4,5] . For all these applications, it is important to have a way to predict and control the acidity, which in most of the cases is done by titrating solutions of compounds dissociated in water or organic solvents, and limits the miniaturization of chemical reactions.…”
Section: Introductionmentioning
confidence: 99%